A Case Series of Children With 2019 Novel Coronavirus Infection: Clinical and Epidemiological Features - Jiehao, Cai; Jin, Xu; Daojiong, Lin; Zhi, Yang; Lei, Xu; Zhenghai, Qu; Yuehua, Zhang; Hua, Zhang; Ran, Jia; Pengcheng, Liu; Xiangshi, Wang; Yanling, Ge; et al. (Clinical infectious diseases, 2020)
Abstract We first described the 2019 novel coronavirus infection in 10 children occurring in areas other than Wuhan. The coronavirus diseases in children are usually mild and epidemiological exposure is a key clue to recognize pediatric case. Prolonged virus shedding is observed in respiratory tract and feces at the convalescent stage.